Prognosis of Liposarcoma Patients in Modern ERA: Single-Center Experience - Demir, Metin; Güven, Denizcan; Aktaş, Burak Yasin; Güner, Gürkan; Aktepe, Oktay Halit; Taban, Hakan; Karakaş, Yusuf; Kılıçkap, Sadettin; Kars, Ayşe; Türker, Alev; Dizdar, Ömer (South Asian Journal of Cancer, 2022)
Objective Liposarcomas are relatively rare tumors. Prognostic and predictive factors and treatment options are limited. We herein presented our 10-year experience with liposarcomas.Materials and Methods Adult patients with liposarcoma treated between 2005 and 2015 in our center were included. Demographic and clinicopathologic features of patients were retrieved from patient files.Statistical Analyses Outcomes in terms of disease-free survival (DFS) and overall survival (OS) were assessed along with potential prognostic factors using Kaplan–Meier analyses.Results A total of 88 patients were included. The median age was 52. Rates of well-differentiated (WDLS), dedifferentiated (DDLS), myxoid (MLS), and pleomorphic liposarcomas (PLS) were 42, 9.1, 37.5, and 4.5%, respectively. Only 10% of patients had high-grade tumors and 93% had localized disease. Ninety-six percent of patients (n = 84) underwent surgery. Adjuvant chemotherapy was delivered to 16 patients. The most common regimen was ifosfamide–doxorubicin. Recurrences were observed in 30 patients, 21 had local, and 9 had distant metastasis. Five-year DFS of patients with the localized disease was 68%. All patients with PLS had relapses and those had the highest distant relapse rates among all subtypes. Multivariate analysis showed T stage and grade were associated with DFS. Five-year OS of the entire population was 68%. Five-year OS was 79, 76, 50, and 0% in WDLS, MLS, DDLS, and PLS, respectively (p = 0.002).Conclusion Management of liposarcomas is still challenging. Surgery is the mainstay of treatment. Novel effective therapies are needed, particularly in advanced disease settings.
Keywords: liposarcoma; histologic subtypes; prognosis; surgery; Sarculator